She's No Lady: The Experience and Expression of Gender among Halifax Women Taxi Drivers since World War II - Berry, Kimberly (Urban History Review / Revue d'histoire urbaine, 1998)
"She's No Lady" explores the complex relationship between gender identity and work culture as experienced by women taxi drivers in Halifax. Working in a traditionally male industry, women taxi drivers often attract the attention of the press and the public as an amusing novelty or a scandalous disgrace. These reactions are, in part, the result of the popular perception that masculine and feminine domain are mutually exclusive, restricted to men and women separately and respectively. Furthermore, characterized as highly competitive, independent operators in a dangerous industry, taxi drivers embody a popular image of masculinity. While the place of women is generally considered to be outside of masculine culture, women taxi drivers demonstrate the fluidity of gender cultures as they adeptly navigate the contested terrain of their masculine work-culture. Despite the routine comments and questions from passengers and colleagues alike, most women drivers find a considerable degree of membership within the larger community of drivers, and in this sense become "one of the men"; seen first as taxi drivers and then women.